The impact of adaptive leadership on work engagement - Krén, Heléna; Juhász, Márta (Vezetéstudomány / Budapest Management Review, 2026)
In our dynamically changing world, keeping employees committed is an ongoing economic and organisational challenge, so it is crucial to determine what we can do to keep them engaged and identify the factors contributing to work engagement. Among several individual and organisational aspects, the leader’s personality and behaviour emerge as key predictors of work engagement. From these, engaging leadership has been widely studied and supported, contributing to employees’ positive affective-cognitive experience at work. However, previous research has not yet examined the relationship between adaptive leadership, the associated theoretical model with engaging leadership, and work engagement. After surveying 310 respondents, the authors used linear regression and moderation analysis to examine the relationships among the three constructs. The results suggest that both leadership styles significantly contribute to increasing engagement. Moreover, the joint application of their behavioural repertoires to an appropriate extent can improve followers’ work engagement more intensely.